GOING UKRAINE: A CASE OF HUMAN TRAFFICKING PREVENTION IN PROSOCIAL STYLISTICS INTEGRATED TEACHING - Paliichuk, Elina (The Modern Higher Education Review, 2024)
This paper describes the practical linguistic and pedagogical experience of teaching stylistics for social purposes in Ukrainian (Borys Grinchenko Kyiv Metropolitan University) and French (Université Paul-Valéry Montpellier 3, France) universities. It meets the challenges of integrating the social domain into linguistic and non-linguistics disciplines thanks to various cognitive structures verbalised through literary devices in media discourse. The social impact of teaching Stylistics is predetermined by the necessity of raising awareness of societal wartime issues in Ukraine and abroad. The case study refers to the project on preventing human trafficking implemented with the support of the CEFRES (French Research Center in Humanities and Social Sciences) fellowship program for Ukrainian scholars. The methods of field observations, surveying in the educational process, and discussions on incorporating war-related topics into humanities with European colleagues were applied during the stay at EMMA (Études Montpelliéraines du Monde Anglophone). The results suggest an overview of the content and conceptual interoperability across linguistic and non-linguistic disciplines at Paul Valery Montpellier University 3 and an evaluation of potential cross-cultural pedagogical activities between the universities. The findings uncover insights into the methodological domain of using literary tools (metaphor, storytelling, schemata, and sensory language) to promote student sociolinguistic awareness through learning experiences.